Java Chilli Compress (Piper Retrofractum) is Effective Against Pain Scale in Elderly People with Rheumatoid Arthritis - Amirul Kadafi; Dian Apri Nelyanti; Della Indriyana Yuliana (Midwifery and Nursing Research, 2023)
Background: A health problem often faced by the elderly is rheumatoid arthritis. This disease greatly inhibits a person from carrying out daily activities. Rheumatoid arthritis is one of the common health problems among the elderly and is included in non-communicable diseases that are often experienced by the elderly. The elderly who experiences rheumatoid arthritis experience symptoms of joint pain, aches or tingling, inflammation, joint stiffness in the morning, and joint movement obstacles, which usually often occur in the joints of the hands, elbows, feet, ankles and knees. This can continue continuously and the longer the complaint feels heavier. The onset of pain makes sufferers often afraid to move, because of the pain, activity will be limited. The purpose of the study was to determine the effectiveness of using Javanese chilli compresses on pain scales in elderly people with rheumatoid arthritis. Research methods: Quasy experiment with control group design. Total sampling technique, Sample of 32 respondents, using observation sheets and NRS (Numeric Rating scale) pain rating scale. The Independent Test t-test was used to determine the mean difference between the intervention group and the control group. Results: This study showed that the intervention group averaged a pain scale of 3.25 while the control group averaged a pain scale of 6.31. The results of the Independent Test t-Test obtained p values of 0.000 â‰¤ 0.05. Conclusion: Java chilli compress is effective for reducing pain scale in elderly people with rheumatoid arthritis.